2019
DOI: 10.2141/jpsa.0180065
|View full text |Cite
|
Sign up to set email alerts
|

The A Allele of the Cholecystokinin Type A Receptor Gene g.420 C > A Polymorphism Improves Growth Traits in Amakusa Daioh Cross Chicken

Abstract: Amakusa Daioh cross chickens are F 1 hybrids of restored Amakusa Daioh sires and Kyushu Rhode dams. In the present study, the association between a single nucleotide polymorphism (SNP; AB604331, g.420 C>A) in the cholecystokinin type A receptor gene and growth traits in Amakusa Daioh cross chicken were investigated. We used 72 male and 72 female birds that had hatched on the same day, were raised in the same chicken house, and were fed the same diet ad libitum from day 0 to 17 weeks (wks) of age. Body weight w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Sequential reports from the author's group have shown that a significant difference in allele frequency between low-and high-growth lines was caused by long-term selection for growth perform-ance, and that the A allele of the g.420 C>A SNP in CCKAR improved growth traits within the Hinai-dori breed (Rikimaru et al, 2013(Rikimaru et al, , 2014. A significant association was observed between the g. 420 C>A SNP and growth traits using the Amakusa Daioh cross chicken, an F 1 hybrid between Amakusa Daioh (native to the Kumamoto Prefecture) sires and the Kyushu Rhode dams (Takahashi et al, 2019). This report provides an additional line of evidence that the g.420 C> A SNP is a useful marker and its application is practicable for improving the growth traits of Jidori brand chickens.…”
Section: Horinouchi Et Al: Cckar Snp In Miyazaki Jitokko Chickenmentioning
confidence: 60%
See 1 more Smart Citation
“…Sequential reports from the author's group have shown that a significant difference in allele frequency between low-and high-growth lines was caused by long-term selection for growth perform-ance, and that the A allele of the g.420 C>A SNP in CCKAR improved growth traits within the Hinai-dori breed (Rikimaru et al, 2013(Rikimaru et al, , 2014. A significant association was observed between the g. 420 C>A SNP and growth traits using the Amakusa Daioh cross chicken, an F 1 hybrid between Amakusa Daioh (native to the Kumamoto Prefecture) sires and the Kyushu Rhode dams (Takahashi et al, 2019). This report provides an additional line of evidence that the g.420 C> A SNP is a useful marker and its application is practicable for improving the growth traits of Jidori brand chickens.…”
Section: Horinouchi Et Al: Cckar Snp In Miyazaki Jitokko Chickenmentioning
confidence: 60%
“…In the Amakusa Daioh cross chickens, no significant differences were observed between the A and C alleles in most intervals of the rearing period (Takahashi et al, 2019). In the Miyazaki Jitokko chickens, the effect of the A allele on ADG in the first half of the rearing period was significantly greater than in the second half.…”
Section: Horinouchi Et Al: Cckar Snp In Miyazaki Jitokko Chickenmentioning
confidence: 80%
“…For example, in the distal region of chromosome 4 where CCKAR is located, the CCKAR SNPs— other than g.420 C>A ( Dunn et al , 2013 ) and the SNPs in other candidate genes ( Lyu et al , 2017 )—have been suggested to affect growth traits by studies on resource populations of White Leghorn×commercial broilers ( Dunn et al , 2013 ) and New Hampshire×White Leghorn ( Lyu et al , 2017 ), respectively. Regardless, without doubt, the g.420 C>A SNP is a quality marker for marker-assisted selection to improve growth traits with a wide application range in chickens, since a significant association is reported between the SNP and growth traits in other commercial slow-growing chickens (Amakusa Daioh cross chicken, Takahashi et al , 2019 ; Miyazaki Jitokko chicken, Horinouchi et al , 2019 ; Hinai-jidori chicken, Rikimaru et al , 2019 ; Okuminokojidori chicken, Ishikawa et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot exclude the possibility that the associations that were detected in this study may have resulted from the linkage disequilibrium between the SNP and other linked nuclear DNA polymorphisms that are directly involved in the regulation of growth traits. For example, in the distal region of chromosome 4 where CCKAR is located, the CCKAR SNPs̶ other than g.420 C>A (Dunn et al, 2013) and the SNPs in other candidate genes (Lyu et al, 2017)̶ have been suggested to affect growth traits by studies on resource populations of White Leghorn×commercial broilers (Dunn et al, 2013) the g.420 C>A SNP is a quality marker for marker-assisted selection to improve growth traits with a wide application range in chickens, since a significant association is reported between the SNP and growth traits in other commercial slowgrowing chickens (Amakusa Daioh cross chicken, Takahashi et al, 2019;Miyazaki Jitokko chicken, Horinouchi et al, 2019;Hinai-jidori chicken, Rikimaru et al, 2019;Okuminokojidori chicken, Ishikawa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation